Impoliteness Theory in a Literary Text: A Pragmatic study - Jinan Abdulrazaq Mohammed (مجلة الباحث, 2025)
Linguists can now explore impoliteness thanks to Brown and Levinson's politeness model (1987). Other linguists, such as Culpeper, Bousfield, and Eelen, adopted the opposite approach to politeness, treating it as a complex framework for easing face-threatening acts. In other words, they looked at circumstances where the speaker's purpose is to injure the listener's face rather than moderating face-threatening acts. This research paper will look at the 'impoliteness phenomena' in George Bernard Shaw's Pygmalion in the opposite direction of politeness (1913). It also emphasizes the characters' varied impoliteness methods. It's worth mentioning that the current study is qualitative in nature because it's focused on defining a specific pragmatic occurrence, namely, impoliteness, using Culpeper's model of impoliteness as a theoretical framework for identifying impoliteness in a carefully chosen literary text. As a result, it is hoped that by applying pragmatic analysis to the conversations of fictional characters, a better understanding of the characters will be acquired